PENGUATAN SIKAP EMPATI SISWA MELALUI PROGRAM PEMBIASAAN BERINFAQ DI SMPN 2 TELUKJAMBE TIMUR - Amalya, Kanaya; Hermawan, Iwan; Farida, Nur Aini; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
Empathy is part of the low character of students, therefore, education needs to strengthen empathy for each student through a habituation program that can be used as the most appropriate solution to prevent a decrease in empathy in students. This research aims to find out how to strengthen empathy through the habituation program, to find out the supporting factors and inhibiting factors for strengthening empathy through the habituation program, to determine the impact of strengthening empathy through the habituation program, this research is located at SMPN 2 Telukjambe Timur. This study uses a descriptive qualitative research method. The data collection procedures used are observation, interviews and documentation. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions. Based on the results of this study, it shows that the infaq habituation program has been implemented for approximately 8 years at SMPN 2 Telukjambe Timur. In the implementation of the infaq habituation program, it has been carried out to date due to supporting factors including: 1) Motivation 2) Understanding and the basics of religion become a guideline 3) continuous 4) teamwork. The inhibiting factors are the lack of awareness in students and the non-participation of parents in giving extra pocket money to spend.